Diagnostic Evaluation of 99mTc-TRODAT-1 SPECT in Parkinsonism - Zahra Babaei Aghdam (Tabriz University of Medical Sciences Press, 2021)
Background Parkinsonism as a group of movement disorders, exhibit similar clinical presentation. Therefore, clinically differentiating these diseases is difficult. We investigated the diagnostic value of 99m Tc-TRODAT-1 SPECT in this setting. Due to the fact that this modality has some limitations in imaging small organs like the sub-regions of basal ganglia, we also evaluated the use of anatomical MR imaging along with functional SPECT imaging in parkinsonism. Methods This follow-up diagnostic test evaluation study was performed with 40 patients with the clinical presentation of parkinsonism, and 10 healthy subjects as controls. After administration of the radiopharmaceutical, SPECT images were acquired, then co-registered on MRI. Uptake values were evaluated in basal ganglia semi-quantitatively. Results In this study, 99mTc-TRODAT-1 SPECT was able to differentiate essential tremor and healthy subjects from progressive supranuclear palsy (PSP) and Parkinson’s disease (PD) with a sensitivity of 76.47% and specificity of 100% at a cut-off of 0.53; however, findings were not significant in differentiation of PD from PSP (p >0.05), and the results were similar in SPECT and co-registered MRI/SPECT images. In evaluation of the uptake pattern in basal ganglia, the lateralization of decreased uptake was only seen in PD; and in PSP, the dysfunction was bilateral in all patients. Conclusion 99mTc-TRODAT-1 SPECT is sensitive and specific in diagnosing basal ganglia dysfunction; however, 99mTc-TRODAT-1 SPECT alone or co-registration on MRI are not adequate in differentiation of the etiologies of basal ganglia dysfunction.